1991
DOI: 10.1002/em.2850170209
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the L5178Y mouse lymphoma forward mutation assay: V. Gases and vapors

Abstract: A new protocol for testing vapors and gases in the L5178Y mouse lymphoma assay is presented. Four chemicals, propylene, 1,2-propylene oxide, 1,3-butadiene, and vinylidene chloride, were tested for their mutagenic potential. Cultures were exposed to the chemicals, which were delivered as vapors or gases, for 4 hr, then cultured for 2 days before plating in soft agar with or without trifluorothymidine (TFT), 3 microgram/ml. Each chemical was tested at least twice. Significant responses were obtained with 1,2-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 19 publications
0
15
0
1
Order By: Relevance
“…BD was mutagenic in Salmonella typhimurium strain TA 1530 with metabolic activation (7), and BD gas was weakly mutagenic in the mouse lymphoma assay in the presence of rat liver S9 (8). In laboratory animals, BD can induce chromosomal damage and somatic cell mutations.…”
mentioning
confidence: 99%
“…BD was mutagenic in Salmonella typhimurium strain TA 1530 with metabolic activation (7), and BD gas was weakly mutagenic in the mouse lymphoma assay in the presence of rat liver S9 (8). In laboratory animals, BD can induce chromosomal damage and somatic cell mutations.…”
mentioning
confidence: 99%
“…Various studies indicate that VDC, with metabolic activation, is genotoxic in bacteria, yeast, and fungi (Bartsch et al 2000; Bronzetti et al 1981; Henschler and Bonse 1977). However, genotoxicity studies in mammalian cells have been equivocal (Drevon and Kuroki 1979; McGregor et al 1991), and unlike Vinyl chloride (Whysner et al 1996), DNA adduct formation has not been reported (Whysner et al 1996). Similarly, results were equivocal in the current NTP genotoxicity testing (NTP TR582) (National Toxicology Program 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is not cytotoxic or mutagenic in cultures of mouse lymphoma cells in either presence or absence of a hepatic microsomal activating system (382). In mouse peripheral tissues and hemoglobin, propene is six times less potent an alkylating agent than propene oxide (377).…”
Section: Genetic and Related Cellular Effects Studiesmentioning
confidence: 98%